Enterprise Architecture for Payment System Industry in Industrial Era 4.0 - Prawira, Khairul Thamrin; Makmur, Amelia; Santoso, Handri (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Today online payments are in demand by most people. Because of the practicality of making payments digitally. This phenomenon has encouraged many industries in the field of finance to make breakthroughs in technology to develop marketing through platforms that have been built. Of course, the platform that is built is a platform that is following the business process requirements of the company. Business processes in the finance industry have become a digital payment platform, making companies in the finance sector carry out digital transformations. Processes that have been carried out manually have been replaced with digital and online processes that bring many opportunities to the finance industry. At the same time creating market opportunities for the company. Thus creating a very broad market for companies carrying out digital transformation. Communities benefit from the changes made by the company. The benefit is that people do not need to make payments or transfer funds. No need to queue up payments at the bank or payment counters. By simply clicking on the smartphone, the payment can go directly to the intended account. This revolution in digital finance transformation has both positive and negative impacts. Positive impacts such as the ease of transferring funds, and negative impacts if the company does not carry out protection or cyber security will have an impact on the company and the user community. Therefore, finance companies must protect or secure data while using the payment platform. A lot of education is done for the people who use the payment platform, where the platform must always update the version. For this reason, payment platform provider companies must be able to make continuous changes. Continuous improvement and continuous development make it a must for payment system service operator companies. Related to the description above, payment system companies must implement Enterprise Architecture for the benefit of the company. The result of Enterprise Architecture is a blueprint of all company production components or an Information Technology Blueprint. This is the goal of research on payment systems for companies carrying out digital transformation